Taxonomía, biología reproductiva y usos de rayas de agua dulce (Myliobatiformes: Potamotrygonidae) en el río Amazonas colombiano (2020)
From the revision of 116 specimens of the Potamotrygonidae family collected in the Colombian Amazon River, the four genera described for the family are registered for the study area, with the species Heliotrygon gomesi, Plesiotrygon iwamae, Plesiotrygon nana, Paratrygon aiereba, Potamotrygon constellata, P. motoro, P. orbignyi, P. scobina and P. tigrina. Considering the number of specimens of each of the species, the reproductive biology of Potamotrygon motoro is described, which contributed 50% of the studied individuals, females and males showed respectively allometric and isometric growth, the ovarian fecundity ranged between 4 and 25 eggs, a statistical correlation was established between the number of eggs, their diameter and the female`s width disk (WD). The average size of sexual maturity for females and males was set at 38 and 35 cm AD respectively, the minimum size for sexual maturity was 27,8 cm AD for females and 26,5 cm AD for males. Lakes interconnected to the Amazon River such as those of the Yahuarcaca system, Korea Island and the Post in the Tarapoto system are strategic ecosystems as breeding areas for P. motoro. Due to the particularities of local fisheries, the use of this resource as an ornamental does not denote great importance for the economy of fishermen and gatherers in the region, suggesting that this activity does not generate strong fishing pressure on the species being used, being Potamotrygon motoro, Paratrygon aiereba and Potamotrygon orbignyi, who make the greatest contributions to the mobilization and extraction figures in the study area. This information is essential for the formulation of appropriate management strategies that ensure the sustainable use of the resource, particularly for P. motoro.